2007
DOI: 10.1088/0960-1317/17/7/s12
|View full text |Cite
|
Sign up to set email alerts
|

Diamond and diamond-like carbon MEMS

Abstract: Diamond and diamond-like carbon (DLC) thin films possess a number of unique and attractive material properties that are unattainable from Si and other materials. These include high values of Young's modulus, hardness, tensile strength and high thermal conductivity, low thermal expansion coefficient combined with low coefficients of friction and good wear resistance. As a consequence, they are finding increasing applications in micro-electro-mechanical systems (MEMS). This paper reviews these distinctive materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(104 citation statements)
references
References 111 publications
3
100
0
1
Order By: Relevance
“…For example, Godet et al [36] showed that polymeric a-C:H films exhibiting low mass densities (< 2 g/cm 3 ) and high H content (25%-40%) are grown under low RF bias powers using C2H2 as well as CH4 based ECR discharges while Baby et al [37] found a high average Raman base line slope at lower substrate bias potentials which corresponds to a high H content in the films when they deposited a-C:H films using C2H2/Ar based ICP discharge. In our case similar trends with respect to mass density are observed for films (see Fig.2) grown using HiPIMS+DCMS at Eion = -eVfl, whereas in 100% Ar HiPIMS case (where there is no intentional use of H) the film exhibit higher density at this ion energy values.…”
Section: B Film Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Godet et al [36] showed that polymeric a-C:H films exhibiting low mass densities (< 2 g/cm 3 ) and high H content (25%-40%) are grown under low RF bias powers using C2H2 as well as CH4 based ECR discharges while Baby et al [37] found a high average Raman base line slope at lower substrate bias potentials which corresponds to a high H content in the films when they deposited a-C:H films using C2H2/Ar based ICP discharge. In our case similar trends with respect to mass density are observed for films (see Fig.2) grown using HiPIMS+DCMS at Eion = -eVfl, whereas in 100% Ar HiPIMS case (where there is no intentional use of H) the film exhibit higher density at this ion energy values.…”
Section: B Film Growthmentioning
confidence: 99%
“…As a result of implantation, an increase in the local density of C atoms in the subsurface region occurs which causes a bond rearrangement from weaker C-C sp 2 to stronger C-C sp 3 bonds giving rise to denser phase of a-C as compared to the growth with lower Eion than Ep [5,38]. A further increase in Eion is likely to enhance implantation which in turn would result in an increased mass density of the film.…”
Section: B Film Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…The DC plasma jet chemical vapor deposition can be used for Diamond like carbon films deposition also [28]. Table 1 shows the different properties of diamond films [29][30][31]6]. In this section, we describe diamond-like carbon deposition by plasma which consists of argon (99.998%), hydrogen (99.9%) and CH 4 (99.5%) is used as a carbon source and is mixed into the plasma jet.…”
Section: Preperation Of Diamond Filmsmentioning
confidence: 99%